PENGARUH PENAMBAHAN EKSTRAK DAUN JERUK PURUT PADA EDIBLE FILM BERBASIS KULIT CEKER AYAM TERHADAP KUALITAS SOSIS SAPI: THE EFFECT OF CITRUS LEAF EXTRACT ADDITION TO EDIBLE FILM BASED ON CHICKEN SKIN ON THE QUALITY OF BEEF SAUSAGE - Sodiq, Fery Ahmad; Abdurrahman, Zakaria Husein; Purwadi, Purwadi (Tropical Animal Science, 2023)
This study aims to compare the sensory or organoleptic, hedonic and microbiological qualities of beef sausages coated using edible film made from chicken feet skin and added with kaffir lime leaf extract at 0%, 0.5% and 1%. The variables observed were color, aroma, texture, taste and aftertaste. The research was carried out in July 2023 in the laboratory of the Boyolali Veterinary Public Health Service Center and tested on panelists at Boyolali University. Organoleptic and hedonic tests in this study used a completely randomized design with 3 treatments and 25 replications. This treatment consists of P1 = sausage coated with edible film with the addition of 0% kaffir lime leaf extract, P2 = 0.5% kaffir lime leaf extract, and P3 = addition of 1% kaffir lime leaf extract. The results of the ANOVA sensory test showed that the addition of kaffir lime leaf extract to the edible film used to wrap beef sausages did not have a real effect on changes in color and texture, but did have a real effect on changes in aroma and taste. In the liking test, only the Aftertaste test showed a real effect, while the color test, aroma test, texture test and taste test did not show a real effect. Testing the number of microbes through the Total Plate Count (TPC) test showed that the addition of 0.5% lime leaf extract was able to maintain the quality of beef sausages until the 6th day of room temperature storage.